Asas Publisitas Perjanjian Perkawinan (Post Nuptial Agreement): Konsep kepastian dan perlindungan hukum bagi pihak ketiga - W. Werdiningsih (Jurnal Ilmu Kenotariatan, 2023)
Marriage agreements after Constitutional Court Decision Number 69/PUU/XII/2015 have a different concept regarding marriage agreements. A prenuptial agreement expanded to a postnuptial agreement has several problems, namely regarding the publicity of the marriage agreement. The validity of post-nuptial agreements can create uncertainty for third parties regarding the husband and wife's assets. Based on these legal issues, this article aims to determine the formulation of the principle of publicity in arranging marriage agreements (Post Nuptial Agreements) so that they have binding force and provide legal protection to third parties. This research uses normative juridical methods, and there are three approaches used, including: statutory approach; conceptual approach, historical research approach; case approach and comparative approach. The implementation of making marriage agreements in marriages, especially for mixed marriages, still raises doubts. This is due to weaknesses in the formulation of legal rules in the Constitutional Court Decision in the form of unclear norms related to Article 29 of the Marriage Law, as well as the absence of clear and firm regulations regarding the Constitutional Court Decision. Therefore, validation is an important element that must be fulfilled by the parties. On the other hand, there is a vague meaning of the word ratified in Article 29 paragraph (1) of the Marriage Law which is intended simply to be a marriage agreement or intended to be announced to a third party or other party. Conclusion The urgency of building a concept of legal protection for creditors, in order to provide guarantees of justice, certainty and legal protection in the context of the birth of mortgage rights, through registration as a fulfillment of the principle of publicity which provides a position as a preferred creditor, in particular providing convenience for creditors in obtaining their rights back. KEYWORDS: SKMHT, Time Limit, Creditors